Analysis of students’ question types in biology learning using problem based learning integrated with ‘questions-students-have’ strategy - Hasna Chairunnisa; Zulfiani Zulfiani (JPBIO (Jurnal Pendidikan Biologi), 2021)
Students' thinking abilities can be identified through the questions they ask during the learning process. This study aims to analyze the types of students’ questions with the Problem Based Learning model integrated with ‘Questions-Students-Have’ (QSH) strategy. This study was conducted at SMAN Tangerang Year XI MIA 3. The research method used was descriptive research. Sampling was in the form of non-probability sampling with purposive sampling technique. Instruments were in the form of teacher observation sheets, student observation sheets, and student worksheets. The data analysis technique was done by quantitative descriptive. The result of this study is the Problem Based Learning model integrated with the ‘Questions-Students-Have’ strategy can stimulate students to ask questions and be able to improve students' ability to ask questions.